Correlation between emotional intelligence and academic achievement among undergraduate nursing students - Wafa Hamad ALmegewly; Amal Rawdhan; Marwah Saleh; Mona Alrimal; Rahaf Alasmari; Shahad Alhamad; Reyuof Almuqri; Morooj Aljebreen; Haya Alsubaie; Sally Mohammed Farghaly Abdelaliem (Elsevier, 2022)
Background: Emotional intelligence has become an appropriate critical base within the educational and health care field. Emotional intelligence is recognized as more than a collection of professional abilities or competencies that affect students' ability in managing their emotions. Purpose: The aim of the current study is to examine the correlation between emotional intelligence and academic achievement among undergraduate nursing students. Methods: A quantitative descriptive correlational design was conducted using a convenience sample of nursing students (n = 204) from all levels in nursing college at Princess Nourah bint Abdulrahman University, Riyadh. The used scale was Schutte Self-Report Emotional Intelligence scale. Results: Emotional intelligence (r = 0.279) was significantly correlated (<0.001) with academic achievement among undergraduate nursing students. Conclusions: Princess Nourah bint Abdulrahman University nursing students with excellent academic achievement had a high level of emotional intelligence.